Analisa Kesiapan Usaha Mikro Kecil Dan Menengah Dalam Penyusunan Laporan Keuangan Sesuai Standar Akuntansi Keuangan dan Penerapan SAK EMKM Pada Laporan Keuangan UMKM. (Studi Kasus Pada UMKM Laundry Box di Kota Batam) - Ita Mustika; Ferdila Ferdila (CERED Indonesia Institute, 2022)
The data sources used are primary data in the form of interviews and documentation of transaction evidence. The results of the study based on the indicators made showed that the Laundry Box SMEs did not implement SAK EMKM in their financial statements for several reasons, namely they did not know about SAK EMKM because they had never received socialization from any party, then in the recording process it was still based on cash and human resources, namely officers the accounting department who understands the preparation of financial statements but is not sufficient to prepare financial statements in accordance with SAK. However, in terms of implementing the business entity concept, Laundry Box has implemented this SAK EMKM. HR accounting department has made two types of financial reports, namely balance sheets and profit and loss and carried out the procedures for recording transactions and the stages of preparing financial statements, although the process did not meet financial accounting standards. Furthermore, this research also produces financial reports that are in accordance with EMKM financial accounting standards.